International Conference on Indoor Positioning and Indoor Navigation 2013
DOI: 10.1109/ipin.2013.6817913
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance analysis of an indoor position tracking technique for smart rollators

Abstract: Abstract-This paper presents a position tracking technique based on multisensor data fusion for rollators helping elderly people to move safely in large indoor spaces such as public buildings, shopping malls or airports. The proposed technique has been developed within the FP7 project DALi, and relies on an extended Kalman filter processing data from dead-reckoning sensors (i.e. encoders and gyroscopes), a short-range radio frequency identification (RFID) system and a front Kinect camera. As known, position tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…To a first approximation, some experiments conducted using real sensors generally confirm this assumption, although the joint probability density function associated with RFID tag detection exhibits more a uniform quasi-circular symmetry around the tag than a Gaussian shape [19]. Stationarity is not an issue for EKFs.…”
Section: Extended Kalman Filter Formulationmentioning
confidence: 87%
See 2 more Smart Citations
“…To a first approximation, some experiments conducted using real sensors generally confirm this assumption, although the joint probability density function associated with RFID tag detection exhibits more a uniform quasi-circular symmetry around the tag than a Gaussian shape [19]. Stationarity is not an issue for EKFs.…”
Section: Extended Kalman Filter Formulationmentioning
confidence: 87%
“…Passive RFID tags are inexpensive, have a limited reading range and can be stuck on the floor at known positions to adjust the estimated coordinates, regardless of the number of people in the environment. Although the idea of using passive RFIDs for localization is not new [10], [16], [17], the solution presented in this paper extends and improves the general idea described in [18], [19], by estimating and compensating possible systematic contributions due to leftside/right-side differences. Unfortunately, the tags cannot provide any direct measure about the direction of motion, and a gyroscope alone is not able to observe orientation.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Assuming, to a first approximation, that the probability of reading a tag is constant within the circle centered in the tag itself and with radius R equal to the maximum nominal range of the RFID reader, then the uncertainty contributions associated with coordinates x and y are uncorrelated and σ 2 x k = σ 2 y k = R 2 /4 [23].…”
Section: B Measurement Model Descriptionmentioning
confidence: 99%
“…In Section III, the localization problem is formulated and the underlying system and measurement models are described. Such models partially derive from the results of preliminary studies reported in [22] and [23], but they have been improved in order to estimate and compensate the effect of possible left-/right-side mechanical asymmetries of the device. Section IV focused on the description of the chosen estimator.…”
mentioning
confidence: 99%